Die forcierte Säkularisierung und ihre Nachwirkung. Das Bildungserbe der DDR am Beispiel Religiöser Jugendfeiern in Ostdeutschland - Handke, Emilia (Zeitschrift für Pädagogik und Theologie, 2019)
In the GDR, forced secularization led to a complex habitual posture of distance vis-à-vis explicit forms of religion and religious communitization. In order to initiate processes of religious communication and learning among families with no confessional affiliation, the church developed and shared responsibility for religious ceremonies for adolescents as an alternative to the secular »Jugendweihe« (coming-of-age-ceremony). These religious ceremonies were offered as a ritual in-between secular and religious traditions in order for the church to regain relevance for a broader part of the population.